FEMINISTIC RESPONSES TOWARD PATRIARCHAL SOCIETY IN JANE AUSTEN’S EMMA - Dessy Perdana Putri; Dwi Aji Prajoko (Humaniora Scientia, 2020)
The  objectives  of  this  study  entitled  Feministic  Responses  Toward  PatriarchalSociety in Jane Austen Emma are (1) To describe patriarchal culture in Jane AustenEmma (2) To describe feministic responses toward the patriarchal culture in JaneAusten Emma (3) To describe the effects of Emma’s feministic point of views. Thewriter used document analysis to analyze the analysis. The main data is taken fromnovel  of Emma.  Some  theories  used  to  analyze  the  data  are Character,  Setting,Patriarchal Society, and Feminism. Moreover, the approaches used in thisresearch are sociological approach and historical approach. For the result, theresearcher finds Emma’s feministic response toward patriarchal society, the effect ofEmma’s feministic point of view after seeing this patriarchal society EmmaWoodhouse would have been breaking this rule. Emma decide that without men shewas already have anything such as wealth and social status. She even marrying Mr.Knightley which is based on love.